\(\Leftrightarrow a^3+b^3+c^3-3abc>=0\)
\(\Leftrightarrow\left(a+b\right)^3+c^3-3ab\left(a+b\right)-3abc>=0\)
\(\Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ac\right)>=0\)
\(\Leftrightarrow2a^2+2b^2+2c^2-2ab-2bc-2ac>=0\)(vì a+b+c>0)
\(\Leftrightarrow\left(a-b\right)^2+\left(a-c\right)^2+\left(b-c\right)^2>=0\)(luôn đúng)
\(a^3+b^3+c^3\ge3abc\\ \Leftrightarrow\left(a+b\right)^3-3ab\left(a+b\right)+c^3-3abc\ge0\\ \Leftrightarrow\left(a+b+c\right)\left(a^2+2ab+b^2-ac-bc+c^2\right)-3ab\left(a+b+c\right)\ge0\\ \Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)\ge0\)
Vì \(a,b,c>0\Leftrightarrow a+b+c>0\)
Lại có \(a^2+b^2+c^2-ab-bc-ca=\dfrac{1}{2}\left[\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2\right]\ge0\)
Nhân vế theo vế ta được đpcm
Dấu \("="\Leftrightarrow a=b=c\)
⇔a3+b3+c3−3abc>=0⇔a3+b3+c3−3abc>=0
⇔(a+b)3+c3−3ab(a+b)−3abc>=0⇔(a+b)3+c3−3ab(a+b)−3abc>=0
⇔(a+b+c)(a2+b2+c2−ab−bc−ac)>=0⇔(a+b+c)(a2+b2+c2−ab−bc−ac)>=0
⇔2a2+2b2+2c2−2ab−2bc−2ac>=0⇔2a2+2b2+2c2−2ab−2bc−2ac>=0(vì a+b+c>0)
⇔(a−b)2+(a−c)2+(b−c)2>=0⇔(a−b)2+(a−c)2+(b−c)2>=0(luôn đúng)
áp dụng định lý cô-si cho số dương
\(a^3+b^3+c^3\ge3\sqrt[3]{a^3.b^3.c^3}=3abc\left(đpcm\right)\)